Pervasive 3′-UTR Isoform Switches During Mouse Oocyte Maturation - He, Yuanlin; Chen, Qiuzhen; Zhang, Jing; Yu, Jing; Xia, Meng; Wang, Xi (Frontiers in Molecular Biosciences, 2021)
Oocyte maturation is the foundation for developing healthy individuals of mammals. Upon germinal vesicle breakdown, oocyte meiosis resumes and the synthesis of new transcripts ceases. To quantitatively profile the transcriptomic dynamics after meiotic resumption throughout the oocyte maturation, we generated transcriptome sequencing data with individual mouse oocytes at three main developmental stages: germinal vesicle (GV), metaphase I (MI), and metaphase II (MII). When clustering the sequenced oocytes, results showed that isoform-level expression analysis outperformed gene-level analysis, indicating isoform expression provided extra information that was useful in distinguishing oocyte stages. Comparing transcriptomes of the oocytes at the GV stage and the MII stage, in addition to identification of differentially expressed genes (DEGs), we detected many differentially expressed transcripts (DETs), some of which came from genes that were not identified as DEGs. When breaking down the isoform-level changes into alternative RNA processing events, we found the main source of isoform composition changes was the alternative usage of polyadenylation sites. With detailed analysis focusing on the alternative usage of 3'-UTR isoforms, we identified, out of 3810 tested genes, 512 (13.7%) exhibiting significant switches of 3'-UTR isoforms during the process of moues oocyte maturation. Altogether, our data and analyses suggest the importance of examining isoform abundance changes during oocyte maturation, and further investigation of the pervasive 3'-UTR isoform switches in the transition may deepen our understanding on the molecular mechanisms underlying mammalian early development.